Profiles and support in student readiness - Widyaning Hapsari; Fazreena Mansor; Purba Rhisma Sutikno (Universitas Sebelas Maret, 2025)
This study explores student learning readiness for implementing the Independent Curriculum, focusing on the transition from home to school and the role of family support. It aims to identify learning profiles, including styles and motivation, and assess family social support as a key factor. Using a descriptive quantitative approach, data were collected from 550 students in grades X–XII at SMAN 1 Wadaslintang through surveys on learning styles, motivation, and family support, analyzed with SPSS 26.0. The results reveal that most students have high motivation and strong family support, with kinesthetic and visual learning styles dominating. Female students show higher motivation and support levels than males. These findings suggest that students with high motivation, suitable learning styles, and supportive families are better prepared for the curriculum transition. The study highlights the importance of understanding individual learning profiles and family support to facilitate successful curriculum implementation, contributing to enhanced competency-based education. Limitations include the sample size and scope, which may affect generalizability. Future research should explore these factors using longitudinal designs to assess causality and include diverse school settings to enhance generalizability. Additionally, qualitative studies could provide deeper insights into student and family experiences during curriculum transitions.